Reliability of shear wave elastography ultrasound to assess the supraspinatus tendon: An intra and inter-rater in vivo study. (February 2020) - Hackett, Lisa; Aveledo, Ricardo; Lam, Patrick H; Murrell, George AC
Introduction: Shear wave elastography ultrasound is a relatively new technique that evaluates the tissue elasticity by applying an acoustic radiation force impulse. It is undetermined how reliable this modality is in assessing rotator cuff tendons. The aim of this study, therefore, was to evaluate the reliability of shear wave elastography ultrasound to assess the stiffness of normal and tendinopathic supraspinatus tendons. Methods: An inter- and intra-rater reliability trial was carried out using shear wave elastography to assess the supraspinatus tendon at its distal insertion, by measuring shear wave velocity and elasticity. Twenty participants with a mean age of 37 (21–69) years old were evaluated. Ten subjects with normal supraspinatus tendon and 10 subjects with tendinopathic tendon were selected. The Virtual Touch Imaging Quantification program was used to generate the acoustic radiation force impulse and to obtain the elastography data. Three raters with different experience in conventional ultrasound were used for the inter-rater trial in normal tendons and the most experienced rater examined all subjects for the intra-rater reliability evaluation. Each rater obtained three readings in three different examinations per subject over a one-week period. Results: The mean (±SEM) shear wave velocity for the normal supraspinatus tendon was 9.96 ± 0.02 m/s (=297 kPa), while in the tendinopathic supraspinatus tendon was 8.3 ± 0.2 m/s (=207 kPa) (p < 0.001). The intra-rater trial agreement was excellent, with an intraclass correlation coefficient = 0.96. In the inter-rater testing, the mean shear wave velocity in normal tendons was 9.90 ± 0.07 m/s (=294 kPa), with intraclass correlation coefficient = 0.45. Conclusion: Shear wave elastography ultrasound was able to show that tendinopathic tendons were less stiff than normal tendons. It was a reliable imaging technique to assess the supraspinatus tendon, especially when used by a single experienced musculoskeletal sonographer.